Do PEJI ao Protestantismo: pluralismo e identidade religiosa afro-quilombola da comunidade Sitio Castainho-Garanhuns-PE. - Nascimento, Cláudio Pereira do (2021)
In this study we approach the effects of religious pluralism on the Afro -quilombola religious identity of the Sítio Castainho - Garanhuns-PE community. Thus, we investigate how religious pluralism has influenced the construction of religious identity, and how religious practices and representations are related or influence the way of life, the forms of organization and community identification. For that, as a theoretical framework, we use the concepts of Zygmunt Bauman of Modernity and Community, the concept of identity by Stuart Hall, and Crisis of meaning and pluralism by Peter Berger. In the methodological contribution we use the qualitative approach for the investigation, with characteristics of exploratory and explanatory nature. Thus, we have appropriated the use of bibliographic research by authors and scholars on the subject, in addition to conducting questionnaires, with residents, community leaders and religious leaders. Data collection was carried out through a video conference on the Google meet platform, through which we interviewed 12 participants, among them: elderly quilombolas, young people living in the community and the pastor of the fundamentalist Presbyterian church. The methodology allowed us to describe and analyze the contemporary organization of the group, providing us with data collection that made it easier to answer the problems raised in this study. In this sense, the aforementioned study points out that religious pluralism has been causing transformations in the religious and cultural identity of the community of Castainho, and, consequently, a crisis of meaning in the group's identity references. In other words, there has been a decline in the cults of the Afro -descendant religion as a form of social representation.